Microwave-synthesized Mg+2 doped jute fibers and their application as a reinforcement in biocomposites. (15th September 2020) - Chaitanya, Saurabh; Cheedarala, Ravi Kumar; Song, Jung Il
Abstract: This study explores the feasibility of treating Jute fibers with a novel treatment process prior to their incorporation into vinyl ester matrix to develop biocomposites. The Jute fibers were treated in-situ within the aqueous solution of Magnesium Nitrate and Sodium Hydroxide in the presence of microwave irradiations. This treatment significantly enhanced the flame retardancy of the Jute fibers determined by micro-calorimeter and thermogravimetric analysis. The grafting of Mg +2 was confirmed by Fourier Transform Infrared Spectroscopy, Energy Dispersive Spectroscopy, and Inductive Coupled Plasma - Optical Emission Spectroscopy. The tensile and flexural properties were observed to significantly improve after the incorporation of Mg +2 doped Jute fibers treated with 0.25 M solution. The fractographs of failed tensile and impact test specimens revealed an improvement in interfacial bonding between the treated fibers and the matrix. The flame retardancy of the biocomposites marginally improved after the incorporation of Mg +2 doped jute fibers.